KELAYAKAN PENGEMBANGAN MULTIMEDIA INTERAKTIF RAMAH ANAK UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP DAN KARAKTER CINTA TANAH AIR SISWA KELAS IV SD - Melani Septi Arista Anggraini; E. Kus Eddy Sartono (Kwangsan: Jurnal Teknologi Pendidikan, 2019)
The purpose of the research was to produce  development of  child-friendly interactive multimedia to improve the understanding of the concept and character of loving the country for fourth grade of elementary school student feasibility. The type of research that already done conducted is Research and Development through 10 stapes, 1) research and information collecting; 2) planning; 3) develop preliminary form of product; 4) preliminary field testing; 5) main product revision; 6) main field testing; 7) operasional product revision; 8) operational field testing; 9) final product revision; and 10) implementation and dissemination. The results of the research conducted show that the development of child friendly interactive multimedia products to improve the understanding of the concept and character of homeland love for grade IV elementary school students is "very feasible" to use. The following results of the validation by the expert judgement get a value of 91 from a maximum score of 100 so that it can be stated that the products developed in the category of "very feasible".The result of validation by media experts got a value of 113 from a maximum score of 128 so that it can be stated that the products developed in the category of "very feasible". Furthermore, students and teachers respond and fall into the category of "very feasible" in the development of  child-friendly interactive multimedia. ABSTRAKPenelitian ini bertujuan untuk  menghasilkan multimedia interaktif ramah anak yang layak.  Jenis penelitian yang sudah dilaksanakan yaitu penelitian dan pengembangan atau Research and Development (R&D) yang melalui 10 tahap yaitu: 1) penelitian dan pengumpulan informasi; 2) perencanaan; 3) pengembangan produk awal; 4) uji coba lapangan awal yang dilaksanakan di SDN Pakel menggunakan 12 subjek; 5) revisi uji coba lapangan awal; 6) uji coba lapangan utama yang dilaksanakan di SDN Mendungan 2 menggunakan 30 subjek; 7) revisi uji coba lapangan utama; 8) uji coba lapangan operasional yang dilaksanakan di SDN Kotagede 3 dan SDN Glagah menggunakan 60 subjek; 9) revisi uji coba lapangan operasional; dan 10) diseminasi yang dilaksanakan secara tervatas dan diperluas. Hasil penelitian yang dilakukan menunjukkan bahwa pengembangan produk multimedia interaktif ramah anak untuk meningkatkan pemahaman konsep dan karakter cinta tanah air siswa kelas IV SD “layak” digunakan. Hasil validasi oleh ahli materi dinyatakan bahwa produk yang dikembangkan dalam kategori “sangat layak”. Hasil validasi oleh ahli media dinyatakan bahwa produk yang dikembangkan dalam kategori “sangat layak”. Selanjutnya, siswa dan guru memberikan respon dan masuk dalam kategori “sangat layak” pada pengembangan produk multimedia interaktif ramah anak.